Both Gender and Inflammatory Status play a Role in the low-dose Rontgen Therapy Effect on Synovial Fibroblasts - Völlings, Antonia; Piltz, Margaux; Titova, E.; Wolff, Teresa; Weissmann, Thomas; Fietkau, Rainer; Frey, Benjamin; Gaipla, U.; Deloch, Lisa (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)
CRIS-Team WoS Importer:2022-06-03

The various functions and phenotypes of macrophages are also reflected in their responses to irradiation: A current overview - Deloch, Lisa; Rückert, Michael; Weissmann, Thomas; Lettmaier, Sebastian; Titova, Eva; Wolff, Teresa; Weinrich, Felix; Fietkau, Rainer; Gaipl, Udo (International Review of Cell and Molecular Biology, 2023)
Macrophages are a vital part of the innate immune system that are involved in healthy biological processes but also in disease modulation and response to therapy. Ionizing radiation is commonly used in the treatment of cancer and, in a lower dose range, as additive therapy for inflammatory diseases. In general, lower doses of ionizing radiation are known to induce rather anti-inflammatory responses, while higher doses are utilized in cancer treatment where they result, next to tumor control, in rather inflammatory responses. Most experiments that have been carried out in ex vivo on macrophages find this to be true, however in vivo, tumor-associated macrophages, for example, show a contradictory response to the respective dose-range. While some knowledge in radiation-induced modulations of macrophages has been collected, many of the underlying mechanisms remain unclear. Due to their pivotal role in the human body, however, they are a great target in therapy and could potentially aid in better treatment outcome. We therefore summarized the current knowledge of macrophage mediated radiation responses.
CRIS-Team Scopus Importer:2023-04-07
Keywords: Immune cells; Immunology; Low-dose radiotherapy; Macrophage polarization; Macrophages; Radiotherapy; Rheumatoid arthritis; Tumor associated macrophages